Finding the right partners for innovation networks - Rusanen Helena (Finland, 2022)
Despite recognition of the importance of careful partner selection for innovation networks, criteria that managers could apply in partner evaluation have gained scarce attention in research. A case study of five innovation processes in networks provided a rich data to explore the partner evaluation criteria that consider the peculiarities of open innovation. The findings suggest that partner selection criteria as discussed in current innovation literature are inadequate to capture the requirements of interactive collaboration. Instead, this study suggests that criteria based on capabilities provide more value when selecting partners for collaborative innovation. These characteristics can be divided into skills, attitudes and knowledge resources that enhance innovating in networks. This study contributes to open innovation and innovation network literature by showing how the capabilities that consist of a specific set of skills, attitudes and resources provide a suitable criteria for the partner selection in inter-organizational innovation networks.
XXIV ISPIM Conference, Innovating in Global Markets: Challenges for sustainable growth